(untitled) (GYMNASIUM, 2017)
The aim of our study is to investigate the anthropometric and morphological characteristics of junior track and field athletes and to determine the differences between genders or events. This study included 20 athletes: 10 girls (age=16.20±0.42 years; height=164.45±5.46 cm; weight=52.25±5.68 kg) and 10 boys (age=16.60±0.51 years; height=173.9±5.21 cm; weight=62.52±5.78 kg) who attend running events at LPS Iași. Based on the anthropometric measurements, we calculated the following indices: of nutrition, of harmony, of robustness, of exploring the functional status of the body and of breathing. T test on the equality of means revealed the existence of significant differences between genders on Erisman Index and abdominal tonicity, where p˂0.05.